Exploring the electrophysiological correlates of the default-mode network with intracerebral EEG - Jerbi, Karim; Vidal, Juan R.; Ossandon, Tomas; Dalal, Sarang S.; Jung, Julien; Hoffmann, Dominique; Minotti, Lorella; Bertrand, Olivier; Kahane, Philippe; Lachaux, Jean-Philippe (Frontiers in Systems Neuroscience, 2010)
While functional imaging studies allow for a precise spatial characterization of resting state networks, their neural correlates and thereby their fine-scale temporal dynamics remain elusive. A full understanding of the mechanisms at play requires input from electrophysiological studies. Here, we discuss human and non-human primate electrophysiological data that explore the neural correlates of the default-mode network. Beyond the promising findings obtained with non-invasive approaches, emerging evidence suggests that invasive recordings in humans will be crucial in order to elucidate the neural correlates of the brain’s default-mode function. In particular, we contend that stereotactic-electroencephalography (SEEG), which consists of implanting multiple depth electrodes for pre-surgical evaluation in drug-resistant epilepsy, is particularly suited for this endeavor. We support this view by providing rare data from depth recordings in human posterior cingulate cortex and medial prefrontal cortex that show transient neural deactivation during task-engagement.